Transformasi UMKM Melalui Industri Kreatif: Pendekatan Untuk Meningkatkan Daya Saing dan Inovasi - Andy Endra Krisna (Jurnal Publikasi Ilmu Manajemen, 2024)
This study explores the role of creative industries in transforming Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to increase competitiveness and innovation. MSMEs are important pillars in the national economy, but they face significant challenges in the era of globalization, such as increasing competition and limitations in resources and market access. The creative industry can act as a catalyst that helps MSMEs innovate and adapt their products and services to evolving market needs. This study analyzes the potential synergy between MSMEs and creative industries to generate added value through creativity, unique skills, and innovative approaches. The results of the analysis show that creative approaches enable MSMEs to strengthen their market position and make significant contributions to the national economy. The implications of these findings highlight the importance of government and related sector support in providing a conducive ecosystem for collaboration, access to technology, and capacity building. This study provides insights into relevant strategies and policies to promote the sustainability and growth of MSMEs through innovation integrated with the creative industry.